Farmers' selection model in a club value chain: The case of the Agro-Pontino kiwifruit industry - Mara Lai; Luca Cacchiarelli; Carlo Russo; Alessandro Sorrentino; Gaetana Petriccione (Italian Review of Agricultural Economics (REA), 2022)
Club varieties are protected horticultural varieties that farmers can grow only with the agreement of the intellectual property right holder (breeder). They contribute to the development of vertically coordinated value chains where breeders act as leading firms, because they can control both production and marketing of the protected variety. Despite the breeders' bargaining power, farmers find club contractual conditions more favourable than those usually offered for non-patented varieties. We hypothesize that breeders may have no incentive to contract all interested farmers in order to avoid expanding production and take advantage of the legal monopoly granted by current regulations. Thus, breeders are expected to select farmers according to an efficiency criterion instead of just licensing all applying farmers. Empirical results from the Agro-Pontino kiwifruit industry support this hypothesis. The results of a questionnaire, submitted to farmers, and of semi-structured interviews targeting key actors of the kiwifruit supply chains, confirmed the selection hypothesis and allow possible selection criteria applied to identify growers of yellow-flesh kiwifruit to be found. A logit-regression model was run using the questionnaire results, while information collected through the semi-structured interviews guided the identification of variables to be included in the model as well as interpretation of the results.
Keywords: Q13; Q18; 330; Club varieties; kiwifruit; farmers' selection; innovation adoption; value chains